Oil And Underdevelopment Of Rural Communities In The Niger Delta - Arugu, Love Obiani; Sunday, Coastman (Advances in Social Sciences Research Journal, 2020)
The paper examines the relationship between the oil industry and the under development of rural oil producing communities in the Niger Delta region of Nigeria. The discovery of crude oil and gas resources has generated environmental degradation and strife that has retarded the development of the region. It has brought in its wake negative development that has impacted negatively on the development of these rural communities. The activities of the oil industry have degraded the environment of these communities, decimating the flora and fauna, thereby crushing the livelihood of the people. In addition, the activities of the oil industry have engendered unprecedented violence conflict. It has led to killing and destruction of lives and property. Since conflict is antithetical to development, the widespread underdevelopment of rural oil producing communities is the result of the devastation of the environment and the violence conflict visited on the communities by the oil industry.